Pelatihan Implementasi Inventarisasi Bahan Baku UMKM Nasi Pecel Ayam Bakar Narsis Menggunakan EOQ dan ROP - Amelia, Puteri; Qori, Raysa Dylia; Ulfah, Mariah (Jurnal Pengabdian Manajemen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) account MSME Nasi Pecel Ayam Bakar Narsis, established in 2018, was the partner in this community service study. The aim was to optimize raw material inventory management through the application of Economic Order Quantity and Reorder Point methods. The service method used a participatory action research approach, through observation and interviews, inventory system design using EOQ and ROP. Variables such as annual demand and ordering costs were included in the calculations. The results of the service show that there is an increase in inventory capabilities, MSMEs are able to optimize the amount and time of ordering raw materials, reduce operational costs, increase production efficiency, and ensure products are always available. The ultimate outcome of this service not only provides practical solutions for the Nasi Pecel Ayam Bakar Narsis MSME but also offers an approach model that can be used by other MSMEs to manage their stock more strategically and sustainably.